RNA m5C regulator-mediated modification patterns and the cross-talk between tumor microenvironment infiltration in gastric cancer - Zhang, Qiang; Sun, Xiangfei; Sun, Jianyi; Lu, Jiangshen; Gao, Xiaodong; Shen, Kuntang; Qin, Xinyu (Frontiers in Immunology, 2022)
The effect of immunotherapy strategy has been affirmed in the treatment of various tumors. Nevertheless, the latent role of RNA 5-methylcytosine (m5C) modification in gastric cancer (GC) microenvironment (TME) cell infiltration is still unclear. We systematically explore the m5C modification patterns of 2122 GC patients from GEO and TCGA databases by 16 m5C regulators and related these patterns to TME characteristics. Lasso Cox regression was employed to construct the m5Cscore based on the expression of regulators and DEGs, which was used to evaluate the prognosis.All the GC patients were divided into three m5C modification clusters with distinct gene expression characteristics and TME patterns. GSVA, ssGSEA and TME cell infiltration analysis showed that m5Ccluster A, B and C were classified as immune-desert, immune-inflamed and immune-excluded phenotype, respectively. The m5Cscore system based on the expression of 8 genes could effectively predict the prognosis of individual GC patient, with AUC 0.766. Patients with lower m5Cscore characterized by activation of immunity and experienced significant longer PFS and OS. Our study demonstrated the non-negligible role of m5C modification in the development of TME complexity and inhomogeneity. Assessing the m5C modification pattern for individual GC patients will help recognize the infiltration characterization and guide more effective immunotherapy treatment.